2001
DOI: 10.1038/oby.2001.5
|View full text |Cite
|
Sign up to set email alerts
|

Social, Educational, and Psychological Correlates of Weight Status in Adolescents

Abstract: Res. 2001;9:32-42. Objectives: The purpose of this research was to examine the social, educational, and psychological correlates of weight status in an adolescent population. It was hypothesized that obese adolescents would differ on psychological, social, and educational variables compared with their non-overweight peers. Research Methods and Procedures:In this cross-sectional study, a population-based sample of 4742 male and 5201 female public school students in the 7th, 9th, and 11th grades responded anonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
318
6
19

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(364 citation statements)
references
References 54 publications
21
318
6
19
Order By: Relevance
“…Findings from other studies also suggest that obesity is associated with impairment in cognitive functioning and other adverse outcomes in girls but not boys. 10,12,[22][23][24][25] These findings may reflect, at least in part, higher levels of weight concerns and/or a greater susceptibility to weight-related teasing/stigmatization in girls. 7,10 In any case, the findings of the present study indicate the need to monitor the developmental functioning of obese children, both boys and girls, to recognize the developmental, as well as the medical, consequences of childhood overweight, and to implement early intervention programs to optimize children's health.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Findings from other studies also suggest that obesity is associated with impairment in cognitive functioning and other adverse outcomes in girls but not boys. 10,12,[22][23][24][25] These findings may reflect, at least in part, higher levels of weight concerns and/or a greater susceptibility to weight-related teasing/stigmatization in girls. 7,10 In any case, the findings of the present study indicate the need to monitor the developmental functioning of obese children, both boys and girls, to recognize the developmental, as well as the medical, consequences of childhood overweight, and to implement early intervention programs to optimize children's health.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Na adolescência, o sobrepeso/obesidade tem sido associado à presença de fatores de risco para doença arterial coronariana (1) ,níveis elevados de ansiedade e depressão, redução nos níveis de auto-estima e no desempenho escolar (2) .Além disso, representa um forte preditor de obesidade, de doenças cardiovasculares, e mortalidade precoce na fase adulta da vida (3) . O rápido crescimento na prevalência de sobrepeso/obesidade na população jovem tem sido amplamente documentado.…”
Section: Introductionunclassified
“…As BMI increased in students, they received fewer friendship nominations. Another study of 9,943 adolescents reported that obese students were less likely to spend time with friends than were thinner peers (Falkner et al, 2001). After controlling for grade level, race, and socioeconomic status (SES), obese girls were less likely to interact with friends than were nonobese peers, and obese boys were less likely to spend time with friends and more likely to report that they felt their friends did not care about them than were nonobese boys.…”
Section: Psychosocial Consequencesmentioning
confidence: 99%
“…One of the most alarming consequences of obesity in youths may be the increased risk of suicidal behaviors. Several large population-based studies have demonstrated that obese adolescents are more likely to endorse suicidal ideation and attempts than are average-weight peers (Ackard, NeumarkSztainer, Story, & Perry, 2003;Eaton, Lowry, Brener, Galuska, & Crosby, 2005;Falkner et al, 2001). For instance, in their study of 9,943 adolescents, Falkner and colleagues demonstrated that obese girls were 1.7 times more likely to report a suicide attempt in the previous year than were thinner peers, even after controlling for grade level, race, and SES (Falkner et al, 2001).…”
Section: Psychosocial Consequencesmentioning
confidence: 99%